Success factors promote personal selling insurance (Journal of Accounting and Financial Studies ( JAFS ), 2013)
Research seeks to clarify the role of insurance companies to make great efforts for the success of the operation promotional products and to check it out for, there should be questions selling the company offers to salesmen producers and the latter projecting on the ground to serve customers and deal with them in style to earn satisfaction with.        The method was used questionnaire and distributed through selected sample included producers in the company and the other sample Staff Planning and marketing researcher used the style gather the necessary information and subjected to analysis using statistical methods arithmetic, standard deviation and concluded search for a set of results which showed encouraging company and salesmen to advertise insurance products to win customer In light of the findings, the satisfaction